APPLICATION OF SEISMIC INVERSIONS AND SPECTRAL DECOMPOSITION OF KTN FIELD, TAIWAN - Nawawi, Mohammad Aidil (2016)
The Kuan Tien (KTN) Field is known for its gas accumulation in the subsurface. Set of 2D seismic data including the post-stack and pre-stack seismic data of the field were supplied along with the well data of the available wells namely KTN-1. KTN-2, KTN-3, KTN-4A and KTN 4B. To find out the extension of the gas reservoir in the subsurface, post-stack and pre-stack seismic inversion were carried out. The result of the seismic inversions successfully located and delineated the gas reservoir in the subsurface indicated by the presence of low impedance layer observed on the inversion outcome. Rock elastic properties such as VpVs, Poisson ratio, Lambda-rho & Mu-rho value and elastic impedance then were extracted from the seismic inversion to characterized the reservoir by generating various cross plotting using the rock properties extracted from the seismic inversion such as Lambda-rho vs Mu-rho cross plot, VpVs vs P-impedance cross plot, Poisson ratio vs P-impedance cross plot. It was found that there is sand layer that exhibits same properties as the gas reservoir sand which could be the potentially overlooked reservoir. Density log and neutron porosity log cross plot was also generated to test out the porosity of the potential overlooked reservoir and the result showed that this zone has a good porosity rate which further confirmed that it is might be a potentially good reservoir that may contains hydrocarbon fluid though further study and investigation should be carried out. Application of spectral decomposition was carried as well for the post-seismic data to test out the gas indications of the gas reservoir of the KTN Field. Based on the yielded result of the spectral decomposition, the gas reservoir is strongly illuminated at iso-frequency of 35Hz, 40Hz and 45Hz. It can be observed below the gas reservoir that might be the seismic attenuation event due to the presence of the gas accumulation which also can be a good indicator of gas filled reservoir sand.